2015
DOI: 10.1155/2015/812354
|View full text |Cite
|
Sign up to set email alerts
|

Primo Vascular System: An Endothelial-to-Mesenchymal Potential Transitional Tissue Involved in Gastric Cancer Metastasis

Abstract: Gastric cancer is the fourth commonest cancer in the world and the second leading cause of cancer-related death. Investigation of gastric cancer metastasis is one of the hottest and major focuses in cancer research. Growing evidence manifested that primo vascular system (PVS) is a new kind of circulatory system beyond vascular and lymphatic system. Previous researches revealed that PVS is a specific tissue between endothelium and mesenchyme and is involved in cancer, especially in tumor metastasis and regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Second, the PVS group sought to determine the structures in cancer tissues and suggested that the structures could be new cancer metastasis channels in addition to blood and lymphatic vessels [56][57][58][59][60][61][62][63][64][65]. One sub-group of the PVS group reported that, through investigating the new structures in several body parts, they found not only various immune cells but also pluripotent adult stem cells able to repair some injured tissues, the location of which had not been well known [66][67][68][69].…”
Section: New Approaches For Visualization and Medical Applicationsmentioning
confidence: 99%
“…Second, the PVS group sought to determine the structures in cancer tissues and suggested that the structures could be new cancer metastasis channels in addition to blood and lymphatic vessels [56][57][58][59][60][61][62][63][64][65]. One sub-group of the PVS group reported that, through investigating the new structures in several body parts, they found not only various immune cells but also pluripotent adult stem cells able to repair some injured tissues, the location of which had not been well known [66][67][68][69].…”
Section: New Approaches For Visualization and Medical Applicationsmentioning
confidence: 99%
“…Animal studies on human or murine derived metastatic tumors suggested that tumor cells might use the PVS as a means of invasion to remote places, 37 , 43 , 44 , 45 , 46 and development of new PVS around the tumor preceded neovascularization. 47 Further, a study showed that human tumor derived stem cells, which were KLF4 positive, were found in the PVS; and KLF4 is a marker of pluripotent stem cells. 37 Therefore, it was suggested that PVS might provide a niche for cancer stem cells.…”
Section: Stem Cells Of the Pvs And Their Putative Roles In Physiologmentioning
confidence: 99%
“…In 2010, the team renamed the Bonghan system, the primo vascular system (PVS), and until recently, they reported many scientific evidences corresponding to the structures and contents of the BCs and BDs, as well as new findings regarding their distributions and functions that Bonghan Kim's research team (BRT) had not mentioned [ 9 ]. In addition, in the 2010s, other domestic and international teams, influenced by the PVS team, started to report the potential functions of the Bonghan system, which was related to tumor development [ 10 ], cancer metastasis [ 11 , 12 ], and the origin of adult stem cells [ 13 15 ]. In 2013, the BRT's claim was academically reevaluated by international researchers, through the perspective of oriental medicine as well as western science, as a special issue titled “Primo Vascular System: Past, Present, and Future” with 18 articles in Evidence-Based Complementary and Alternative Medicine ( http://www.hindawi.com/journals/ecam/si/954751/ ).…”
Section: Introductionmentioning
confidence: 99%